2022
DOI: 10.3389/fnagi.2022.910231
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sleep Duration and Sensory Impairments Among Older Adults in China

Abstract: ObjectiveStudies of sleep duration in relation to the risk of sensory impairments other than dementia are scarce. Little is known about the associations between sleep duration and sensory impairments in China. This study aims to explore the associations between sleep duration and single or dual sensory impairments (visual and/or hearing).MethodsThis cross-sectional study used the data from 17,668 respondents were drawn from the 2018 survey of the China Health and Retirement Longitudinal Study (CHARLS), an ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The associations were independent of gender, age, marital status, education level, area of residence, smoking status, drinking status, BMI, social participation, baseline health condition and sleep quality. A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The associations were independent of gender, age, marital status, education level, area of residence, smoking status, drinking status, BMI, social participation, baseline health condition and sleep quality. A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27). A recent article revealed an association between nocturnal sleep with ≤ 4 h (OR: 1.53, 95%CI: 1.31, 1.80) and HL in comparison to the 7 h group (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations